(untitled) (Research Journal, 2023)
There are different types of systems in modern countries and governments. Governments are becoming distinct sub-systems. In a federal system, a state’s authority is constitutionally split and governed by lower levels of government. This is opposed to a unitary system, where it is regulated from top to bottom based on law. There are some federal system models in modern countries. At first, the Constitution of United States of America applied federalism to its creation. Central federalism was mandatory for country formation. That is the first contemporary federal system in contemporary governing systems. Despite this, many countries have adopted different federalism models today. Federal systems also have various practices. Since this paper is prepared using the secondary sources of data, it attempts to introduce various models of federal government systems practiced in different countries. It also critically examines the reasons why multiple forms exist within the federal government system.